Various Artists : Andreas Kunzmann - Bärbl Neubauer - Brigitte Kowanz - christine Bader - Dietmar Brehm - Ecke Bonk - Ernst Caramelle - Ernst Schmidt jr. - Eva Schlegel - Ferdinand Schmatz - Franz Vana - Franz West - Gerhard Pakesch/muki - Gerwald Rockenschaub - Gilbert Bretterbauer - Günter Schrom - Heimo Zobernig - Helmut Mark - Herbert Brandl - Herwig Kempinger ; Ilse Haider - Karl Kowanz - Kurt Ryslavy - Paul Renner - Peter Tscherkassky - Peter Weibel - Richard Fleissner - Richard Hoech - Romana Scheffknecht - Rudi Leitner - Rudi Molacek - Rudolf Polanszky - Tina Bepperling - Vlado Honea - Wolfgang Capellari - Wolfgang Hofmann - Wolfgang Schrom. (Oslo : Unge Kunstneres Samfund, 1987)
Andreas Kunzmann - Bärbl Neubauer - Brigitte Kowanz - christine Bader - Dietmar Brehm - Ecke Bonk - Ernst Caramelle - Ernst Schmidt jr. - Eva Schlegel - Ferdinand Schmatz - Franz Vana - Franz West - Gerhard Pakesch/muki - Gerwald Rockenschaub - Gilbert Bretterbauer - Günter Schrom - Heimo Zobernig - Helmut Mark - Herbert Brandl - Herwig Kempinger ; Ilse Haider - Karl Kowanz - Kurt Ryslavy - Paul Renner - Peter Tscherkassky - Peter Weibel - Richard Fleissner - Richard Hoech - Romana Scheffknecht - Rudi Leitner - Rudi Molacek - Rudolf Polanszky - Tina Bepperling - Vlado Honea - Wolfgang Capellari - Wolfgang Hofmann - Wolfgang Schrom
Various Artists, Unge Kunstneres Samfund, Oslo, 31.10 - 22.11.1987
boek